GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 2722861 species occurrences available in GBIF matching the query: All data. The dataset includes 2722861 records from 23580 constituent datasets: 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 7 records from Analyses of the recent components of sediment core PS1277-1. 352 records from Nannofossil abundance of Hole 60-458. 11961 records from MEXU/Leguminosae. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 1097 records from Planktic foraminifera counts of sediment core RC08-49. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 509 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 581 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 6192 records from marine sediment metagenome Metagenome. 561 records from Range table from benthic foraminifers in ODP Hole 146-889A. 45811 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 9 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 21163 records from SEWBReC Bees, Wasps and Ants (South East Wales). 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 80 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2780 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 878 records from COA Bird Collection (Arctos). 154 records from Sorensen distance for herbivores. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 111 records from Total foraminifera counts of multinet M33/1_MSN1029. 118 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 10654 records from Bryophyte specimens of The Nagoya University Museum. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 34518 records from University of Guam Insect Collection. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 22857 records from National Botanic Garden Belgium - Myxomycetes. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 395 records from Planktic foraminifera abundance of Hole 32-310. 26 records from Dinoflagellate abundance of Hole 81-554. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 3247 records from Museu de Ciències Naturals de Barcelona: BGJBB. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 109 records from Nannofossil abundance of Hole 24-232. 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 11424 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 1340 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 1189 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 265 records from Nannofossil abundance of Hole 36-329. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 115 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 22662 records from Microbial community structure and dynamics in the oxygen minimum zone of the Northeast subarctic Pacific Ocean. 256 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 24370 records from Muséum d'Avignon. 626 records from Mycology collection, Norwegian Forest and Landscape Institute. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 235 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 173 records from UWIZM Anoles. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Nothrus pulverulentus. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 444 records from Pollen analysis of sediment profile TR0 from Truennensee. 2451 records from Macrobenthos Chukchi Sea, 1986. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 210 records from Condamine Alliance. 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 5516 records from Comparative study in validity of three regions of 18S-rRNA for eukaryote amplicon sequence analyses. 1385 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 48 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 1701 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 168 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 107 records from Faunal assemblage of sediment core TR149-31. 1626 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 17364 records from Microbial community in marine sediments. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 18 records from Naturtag. 14 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 20627 records from Herbier Louis-Marie (QFA) - Collection de lichens. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 165061 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 93 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 204 records from Planktic foraminifera abundance of Hole 29-284A. 73 records from Planktic foraminifera abundance of Hole 49-409. 607514 records from Plant. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 12859 records from Colecção Entomológica IIA. 1266 records from Actinomycetes Collection in BCRC. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 17155 records from MZFC/Coleccion de Aves. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 52 records from Nannofossil abundance of Hole 10-91. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 6941 records from DMNS Egg Collection (Arctos). 2538 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 14923 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 5783 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Orthoptera - SMF. 238 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 287870 records from Florida Keys Reef Visual Census 2014. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 26 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 1702 records from BioGIS - Bryophytes - HUJ collections. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 672 records from Colección de Entomología - Curculionidae. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 158 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 393 records from Dinoflagellate cyst counts on sediment core ABC26. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 306 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 3 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 22180 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 6237 records from Plecoptera. 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 280 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 34 records from NZCS Brownsberg Nature Park Monitoring. 143 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 62124 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 101 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 25 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 383 records from Neogene palynomorpha from site 81-552. 120 records from BIRDRACE The early birds. 1289 records from RECORD Orthoptera Data. 92 records from Protozoa Abundance_Microbial Parameters. 24 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 55 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 115 records from Antarctic Pycnogonids II. 10 records from Oberservation of birds at station PS14/143 along 49° West. 1763 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 1952 records from ISM Ichthyology Collection. 6979 records from Upper Silesian Museum, Bird Observations. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 1628 records from Données naturalistes de Quentin ROME. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 20025 records from University of California Santa Barbara Invertebrate Zoology Collection. 285 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anhingidae. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 165 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 57 records from CSIRO Yellow Box Fragmentation Project. 673 records from Planktic foraminifera abundance of Hole 45-395. 60022 records from Entomology Collection at the Natural History Museum of Utah. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 1 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 112736 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 3184 records from Herbarium specimens of Limoges university (LIMO). 4847 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 94857 records from Fish specimens of Kagoshima University Museum. 26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 233 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 988 records from flower availability 2008 Alb-korrigiert. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 2808 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 13 records from Dinoflagellate abundance of Hole 14-144. 23 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 7122 records from UTEP Invertebrates (Arctos). 59 records from Schulteich Freie Waldorfschule Darmstadt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 998 records from Korean Ethnobotany Database. 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 481 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 41 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 4 records from Planktic foraminifera abundance of Hole 19-191A. 23643 records from CNIN/Abejas de México/Apoidea. 1331 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 1567 records from Flora útil del Municipio de la Huerta, Jalisco. 3621 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 828 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 2295 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 159 records from Total foraminifera counts of multinet M36/6_MSN1196. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 15 records from Nannofossil abundance of Hole 10-93. 2194 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 12 records from Art´n Vielfalt im Kinderwald. 263 records from Planktic foraminifera counts of sediment core V14-77. 10 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 3724 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 302 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 385 records from Invasive Non-Native Species, Outer Hebrides. 16 records from Benthic macrofauna abundance of sediment core 13077-093. 116446 records from Naturalis Biodiversity Center (NL) - Crustacea. 389 records from Amphibian and Reptilian (KIEE-AR). 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 12147 records from Danish Ants (Formicidae). 25 records from Brown algae specimens of Komatsu City Museum. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 78 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 25098 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 1285805 records from Données issues de Clicnat (Base de données naturaliste picarde gérée par Picardie Nature). 413272 records from DATAVES. 1186 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1810 records from The Broward College Insect Collection. 7 records from Planktic foraminifera abundance of Hole 53-418B. 23552 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 424 records from Distribution of nanoplankton at trap WR2. 1406 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 13624 records from Ecosphère_2017_12_18. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 168538 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 794 records from Isle of Wight non-native invasive species. 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 581 records from Floristic records in the Moscow and Novgorod regions. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 882 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 155 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 735 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 95 records from Kystfuruskoger i Tysnes og Fusa. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 91 records from Diatom abundance of Hole 95-613. 8 records from Die Bachspezies 2008/2009. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 3 records from Results of palynological analysis of Hole 302-M0004C. 45140 records from SIRFF - FNE Centre-Val de Loire - Données 2016. 68 records from Streuobstwiese. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 23 records from Abundance of benthos infauna at station GIK23042-2. 794935 records from Western Australian Museum provider for OZCAM. 1152 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 663 records from Benthic foraminifera counts of sediment core GIK23352-3. 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 31014 records from River Biologists' Database (EPA). 77075 records from CABI Africa Invasive and Alien Species data. 7780 records from Eurobodalla Regional Botanic Gardens. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 7 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 1651 records from Great Eastern Ranges - Slopes to Summit. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 75 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 194339 records from Tiroler Landesmuseum Ferdinandeum. 95 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 6 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 1192 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 78 records from Mammals (GNHM-MM). 8851 records from Odonata records from RSPB Reserves 1970-2009. 1038 records from Données supplémentaires Atlas des Mammifères marins. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 85 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 34332 records from Protist Diversity in the East China Sea. 798 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 223 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 126 records from SEWBReC Springtails and allies (South East Wales). 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 2076 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 49 records from Nannofossil abundance of Hole 9-79. 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 164357 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 31020 records from National Museum of Natural Science. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 234 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 1196 records from Global Ocean Sampling Expedition. 69 records from BIRDRACE Pfeifenten. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 17 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 6158 records from Marine metagenome ICM_JRV. 1575 records from Hermatypic Corals of Western Australia. 322 records from Collections ichtyologiques et herpétologiques (BOUM). 288 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 8516 records from Données naturalistes de Bruno OGER. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 65903 records from Norwegian Lepidoptera working group. 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 38876 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 71 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 308 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 6192 records from NE Scotland fish records 1800-2010. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 301 records from Marine sediment metagenome ICM_GMS. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 648 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 1014 records from Pollen profile ADR353. 97 records from Foraminifera species abundances from tow TT011_7-MOC66. 270 records from bmhs_weatherheadshell_collection. 6 records from Sächsische Schweiz (Pfaffenstein). 11960 records from Données ONEMA BDMAP 2014. 578 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 1026 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 285727 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 220 records from Living Cirripedia. 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 7609 records from Amundsen Gulf Overwintering Eukaryote Community. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 84 records from Roter Berg Werdau (Leubnitz). 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3755 records from Données naturalistes de Charlotte PICARD. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 4 records from Ostracoda abundance of Hole 44-390. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 18 records from Anfibios presentes en el Cerro Jánano. 1715185 records from NBIS Records to December 2016. 149 records from Abundance of radiolaria at station UT99-23-2. 27 records from Planktic foraminifera abundance of Hole 51-417B. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 2676 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 375 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 931 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 103 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 49 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 960 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 22 records from Ostracoda abundance of Hole 24-238. 22 records from Thirteen new records of ferns from Brazil. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 15 records from Meiofauna abundance in sediment core 54301-010. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 435 records from Marine metagenome ICM_AWP. 679 records from Collection Hydrozoa - ZSM München. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 202480 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 121 records from Foraminifera abundance of sediment core IN68-28. 9057 records from NE Scotland other invertebrate records 1800-2010. 152 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. www.faune-guyane.fr. GEPOG & LPO. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 6336 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 15 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 558 records from Foraminifera abundance of Hole 74-526A. 267 records from Dinoflagellate abundance of Hole 81-555. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 725 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 1872 records from Herbier National de Guinée (HNG) (BID-AF2015-0066-REG). 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 651 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 9140 records from EDIT - ATBI in Gemer area (Slovakia). 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 22137 records from Global compendium of Aedes albopictus occurrence. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 186 records from Nannofossil abundance of Hole 27-259. 22053 records from UTEP Vertebrates. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 152 records from AKG-Gelände (Bensheim). 237 records from Planktic foraminifera abundance of Hole 21-207. 12 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 16 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 23 records from Benthic foraminifera abundance of Hole 93-603. 1 records from Occurrence of mammalia relicts at site Raagelund. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 5 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 4926 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 84 records from Ostracoda abundance of Hole 48-403. 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 10699 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 1589 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 16128 records from Colección Ictiológica del Instituto Alexander von Humboldt. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 728 records from Planktic foraminifera counts of sediment core V27-178. 283 records from Antarctic Amphipoda. 210 records from Lebensraum Gesamtschule (Langerwehe). 425 records from Foraminifera abundance of Hole 64-481. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 905 records from Coléoptères Silphidés du département du Loiret. 18094 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 123 records from Total foraminifera counts of multinet M21/2_MSN648. 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 2568 records from Fish (NHMK-PI). 2300 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 31152 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 28 records from Korean Plant Virus Database. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 14 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 29 records from Herbarium Senckenbergianum (FR) - Protista. 3 records from Zoology in the Middle East. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 69319 records from Données de l'Observatoire de la Faune de Bourgogne. 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 1208 records from Microbial diversity studies of Arabian Sea sediment. 18 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 5448 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 321 records from Echinoderms from the Seaflower Biosphere Reserve. 280 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 16 records from Insect Collections of Okomu National Park- Nigeria. 235 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 412 records from Heinersdorfer Sumpfwiese. 133650 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 291402 records from ARABEL - Arachnologia Belgica. 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 23562 records from Arctic Species Trend Index (ASTI) : Marine. 53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 3332 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 33416 records from Wolli Creek Preservation Society Bird Survey. 348 records from Antarctic pycnogonids. 553 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 62776 records from MLZ Bird Collection (Arctos). 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 26 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 166 records from Wiese am Waldrand (Gurtweil). 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 148143 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 351 records from UWYMV Herpetology Collection (Arctos). 14069 records from Midden-Limburg Fish Ponds Survey. 102547 records from Herbarium Senckenbergianum (FR) - Fungi. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 6478 records from National System of Protected Areas in Poland - Animals. 170 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 240 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 2007 records from Plant specimens of Bihoro Museum. 1867 records from Mushroom Collection in BCRC. 158 records from Planktic foraminifera counts at CTD station PS55/063. 2829 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 4193 records from Leicestershire and Rutland Aculeate Records. 177 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 10110 records from Suivi Temporel des Libellules (STELI). 944 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 2712345 records from First Bird Atlas. 1153 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 395 records from Reptilia ZMK. 1383 records from Plant observations from Białowieża National Park. 5406 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 85277 records from University of Ghana - Ghana Herbarium. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 1943 records from Pollen profile RAC20, Lake Racou, France. 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 2807 records from Natura 2000 Vallée de la Seille. 591 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 10898 records from Inventario de Hymenóptera; parasítica en México. 19066 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 22516 records from MfN - Fossil Fish Collection. 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 3 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1798 records from 3Soil16S. 1187 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 67 records from Planktic foraminifera abundance of Hole 9-76. 4126 records from (Table 4) Percentages of planktonic foraminiferal taxa from the 214 surface-sediment samples from the South China Sea and the western Pacific. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 76 records from BIRDRACE Nachtigallen. 68 records from Nannofossil abundance of Hole 24-233A. 3006 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 1286 records from ConDidact Citizen Science Surveys - Amphibians 2007. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 55 records from Dinoflagellate abundance of Hole 28-274. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 96 records from Données naturalistes (Rhopalocères et Zygènes) de Jude LOCK (indépendant). 217 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 50 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 3425 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 495 records from Planktic foraminifera counts of sediment core A15-558. 408 records from Birds Specimens of Akita Prefectural Museum. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 19 records from Données naturalistes de LE GLOANEC Vincent. 57451 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-64, 1974-5. 370 records from Size of planktic foraminifera at CTD station PS55/051. 26841 records from MSUM Ichthyology and Herpetology Collections. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 7122 records from Whale catches in the Southern Ocean. 371 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 16 records from Benthic macrofauna abundance of sediment core 13200-008. 16809 records from Genebank, National Institute of Agrobiological Sciences. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 218 records from Nannofossil abundance of Hole 49-408. 25 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 11 records from Analyses of the recent components of sediment core PS1011-1. 368 records from Biological Recording in Scotland - Bumblebee Survey. 277138 records from Allan Herbarium (CHR). 254268 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 25 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 323 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 6 records from Foraminifera abundance of Hole 58-442. 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 11258 records from Uncultured eukaryotes Targeted Locus (Loci). 253 records from Données naturalistes d'Olivier LAURENT. 24260 records from Restauración y conservación de Isla Guadalupe. 407 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 46 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 5428 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 98 records from Warnowtal (Rostock). 930 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 6 records from Wuhle - Brücke / B1. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 27830 records from Marie-Victorin Herbarium (MT) - Bryophytes. 462 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4). 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 3 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 181 records from Dinoflagellate cysts from sediment core PS1295-4. 111 records from BIRDRACE Die Wendehälse. 88 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1021 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 186 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 8332 records from Scotland Otter Survey Database. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 4 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 3190 records from Utah State University, Intermountain Herbarium. 351778 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 1602 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 922 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 223486 records from Phytochorologie des départements français. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 186 records from Benthic foraminifera and algae abundance of Hole 81-554. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 9902 records from DSMZ Bacteria. 247401 records from CAS Entomology (ENT). 24 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 4126 records from Naturalis Biodiversity Center (NL) - Pisces. 244406 records from Carnet B Lorraine. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 475 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 5 records from Nannofossil abundance of Hole 16-157A. 550 records from Radiolaria assemblage in sediment core GIK23414-6. 386 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 320 records from Myxomycetes collection of the University of Eastern Finland. 321633 records from Seasearch Marine Surveys in England. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 70 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 38 records from Planktic foraminifera abundance of Hole 84-566C. 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 14009 records from Collection Trichoptera - SMF. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 115 records from Nannofossil abundance of Hole 1-3. 235 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 130 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 255 records from Occurrence of mammalia relicts at site Raj Cave. 100 records from Nannofossil abundance of Hole 6-55. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 798 records from Planktic foraminifera abundance of Hole 27-262. 100368 records from Arizona State University Hasbrouck Insect Collection. 3776 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 39 records from Planktic foraminifera abundance of Hole 27-260. 2536 records from Invasive Alien Species Occurrence in Ghana. 3618 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 63364 records from CCAMLR historic KRILL. 89 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 430 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3587 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 87901 records from MDFRC macroinvertebrate survey. 62 records from Amtsrain Apolda-Zottelstedt. 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 179 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 66116 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 36 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 57 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 230 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 108 records from Nannofossil abundance of Hole 31-299. 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 151 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 40 records from Seawater carbonate chemistry and boron incorporation of planktic foraminifer Orbulina universa during experiments, 2011. 9476 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 99 records from Dorfrand Mauderode. 411 records from SuLaMa reptile survey I 2012. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 49 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2787427 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 749 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 164 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 33 records from Waldstück am Schullandheim Bad Bederkesa. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1513 records from M. Gollop Collection. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 53203 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from Données naturalistes d'Olivier DELZONS. 218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 68 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 1 records from Berlese's Primitive Oribatid Mites. 174 records from BIRDRACE Bon(n)apartemöwen. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 452 records from Benthic foraminifera counts of sediment core PS1852-2. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 2606 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 340 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 16 records from Hazel Dormouse in Ireland. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 30 records from Nannofossil abundance in sediment core PS1313-4. 285 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 123 records from Total foraminifera counts of multinet M21/4_MSN694. 844 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 399 records from Planktic foraminifera abundance of Hole 14-142. 39329 records from Insects, Outer Hebrides. 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 46 records from An der Ohm, (Wettsaasen). 49 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 168 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 68 records from Nannofossil abundance of Hole 73-521A. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 2419 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 3 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 91 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 701 records from Range table from benthic foraminifers in ODP Hole 151-913B. 216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 1739 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 1985 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 124 records from Kirkliston Range stream monitoring. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 43066 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 25446 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 5 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 4880 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 5538 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 88 records from Total foraminifera counts from M35/1_MSN1065. 2781 records from Marine Turtles. 196 records from Foraminifera abundance of Hole 33-317A. 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 51 records from Colección de Aráceas del Jardín Botánico San Jorge. 15 records from Conringia orientalis. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 120 records from Total foraminifera counts of multinet M21/2_MSN650. 6 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 159 records from Nannofossil abundance of Hole 67-499B. 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 463 records from Foraminifera abundance of sediment core IN68-9. 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 418 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 182 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 101 records from Naturgrundstück (Eutin). 12127 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 4230 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 61 records from Shrews of Poland. 152 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 9 records from Nannofossil abundance of Hole 2-11. 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 17367 records from K-State Museum of Entomological and Prairie Arthropod Research. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 269 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 2274 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 15 records from Nannofossil abundance of Hole 6-48B. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 277 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 29876 records from European Moth Nights. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 81 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 1826 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 1127 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 68626 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 24795 records from Université d'Aix-Marseille. 931 records from Données naturalistes de Mathilde DUSACQ. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 6 records from MfN - Micropaleontology. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 1036 records from BUND - Dassower See (Lübeck/Dassow). 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 352 records from Birds and plant species near Petushki town (Vladimir region). 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 36 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 984 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 54402 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 4 records from Sächsische Schweiz (Wehlener Gebiet). 113 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 356 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6067 records from Arthur Chapman Observations. 571 records from Cuxhavener Küstenheiden. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 40 records from Planktic foraminifera abundance of Hole 14-137. 2392 records from UWYMV Bird Collection (Arctos). 1616778 records from Hatikka Observation Database. 62 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 200187 records from inatura - Erlebnis Naturschau Dornbirn. 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 386 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 42 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2020 records from Birds (NHMK-BI). 3792 records from Sea water microorganisms Raw sequence reads. 1288808 records from PlutoF platform observations. 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 1500 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 136 records from Total foraminifera counts of multinet M21/6_MSN784. 6 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 103 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 11584 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 107580 records from Database of invertebrates collected in Mongolia. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 1249 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 10075 records from Nematoda of Costa Rica (INBio). 45 records from Nannofossil abundance of Hole 10-89. 32916 records from Insect specimen database of Atsugi City Museum. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 177 records from Nannofossil abundance of Hole 30-285A. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 356 records from Morphologische Daten von Puffinus creatopus. 23648 records from WTSWW Data: All Taxa (West Wales). 614 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 213 records from Pollen record of profile 3TZ. 421246 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 192 records from "Ahrschleife bei Altenahr". 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 499013 records from South Australian Museum Australia provider for OZCAM. 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 35 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 5 records from Coccolith counts of multinet M32/5_MSN981. 100 records from Brock University Herbarium (BU). 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 148 records from Herbarium BSG Hepaticopsida. 220 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 134 records from Pollen record of profile 3TZ2. 1 records from Hoplophora ardua. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 8 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 7128 records from La familia Asclepiadaceae en México. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 311 records from Benthic foraminifera abundance of Hole 41-366A. 373 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 9968 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 111099 records from Suivi Temporel des Rhopalocères de France (STERF). 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3383 records from Lista florística de la Costa Grande del estado de Guerrero. 17 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 144 records from Total foraminifera counts of multinet POS247/2_MSN1386. 411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 23 records from Landwehrbach. 10079 records from CSIRO, fish surveys by the Soela, 1980s. 597 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 61 records from Alien Species in Poland - Plants. 931 records from Microfossil abundance of Hole 16-158. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 406 records from Nannofossil abundance of Hole 78-543. 15000 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1162 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 35 records from Total foraminifera counts of multinet FCA97C_MSN1339. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 383 records from Nannofossil abundance of Hole 66-490. 4400 records from USAC Mammals Collection. 195 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 218 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 733 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 270 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2350 records from Données naturalistes de Bernard Lalanne-Cassou. 363 records from PSUZC-Reptile Collection. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1136 records from Nannofossil abundance of Hole 82-558A. 37 records from Planktic foraminifera counts of sediment core RC13-154. 1513 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 3327 records from BioGIS - Mammals - SPNI. 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 29520 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 91840 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 23 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 917519 records from SEWBReC Birds (South East Wales). 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 216 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 569 records from (App 2) Relative contents of benthic foraminifera species in Holocene sediments from Core ASV11-858-3. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 141 records from Total foraminifera counts from multinet SO119_MSN1285. 5640 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 77414 records from MfN - Fossil vertebrates IV. 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 782 records from Planktic foraminifera abundance of Hole 42-372. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 45947 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3439 records from MEXU/Flora de Oaxaca. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 9743 records from marine sediment metagenome Raw sequence reads. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 287 records from Nannofossil abundance of Hole 66-488. 40 records from Heavy minerals of sediment core PL94-64. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 132045 records from Amphibiens et Reptiles de France (Enquête 2). 3320 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 9304 records from Echinoderm collection of National Museum of Nature and Science. 109176 records from Herps Specimens. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 1450 records from Données naturalistes d'Alain BERLY. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 30535 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 221 records from (Table 6) Ostracod assemblages of sediment core 9409. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 2240 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 1698 records from Red-throated diver national surveys in Scotland - raw data. 215 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 14853 records from Données bibliographiques et opportunistes Mammifères issues du SiRF. 638313 records from Données de la flore d’Alsace (SBA). 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 5046 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 4227 records from Données naturalistes de Loïc SALAUN. 1139 records from SWECO. 1694 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 60101 records from EAC - Herbário Prisco Bezerra. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 2507 records from East Ayrshire Species Database. 2565 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 1200 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 9 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 195 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 30087 records from Collection Crustacea - ZMB. 742 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 1200 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 93 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 36 records from Nannofossil abundance of Hole 25-249. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 4536 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 69 records from Unter hellen Zinnen und finsteren Grotten. 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 6446 records from Modernisation des ZNIEFF du PnrL. 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 129 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0011B. 20 records from Occurrence of mammalia relicts at site Niederlehme. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 86 records from UWIZM Cnidarians. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 152253 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40170 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 148 records from Occurrence of mammalia relicts at site Veternica. 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 1001 records from Mushroom (KIDR-MR). 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 2 records from Benthic foraminifera abundance of Hole 42-376. 887 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Occurrence of mammalia relicts at site High Furlong. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 2862 records from University of Sindh Jamshoro Herbarium. 2924 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 58 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 128 records from Faunal assemblage of sediment core TR149-32. 904 records from Nannofossil abundance of Hole 15-149. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 1913 records from Registros Primates Neotropicales Convocatoria APC. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 631 records from Anammox bacteria in sediment cores of Daya Bay, China. 19 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 77 records from Incorporation of Mg and Sr in calcite of cultured benthic foraminifera (Heterostegina depressa and Ammonia tepida) and seawater carbonate chemistry, 2010. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 1399 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 100 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 154 records from Dermaptera in the icipe collection. 212 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2344 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 109 records from MMFR Zingiberaceae Botanical. 73 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 45872 records from The national database for marine data (MADS). 31 records from Nannofossil abundance of Hole 9-82. 204 records from Foraminifera abundance of Hole 57-440A. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 2327 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 54 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 114 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Groß Klein. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 153 records from Planktic foraminifera abundance of Hole 18-181. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 3444 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 1004 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7). 16 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 337 records from Pollen data of trap CB4. 1481 records from Leicestershire and Rutland Mature trees Inventory 2011. 15 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 52443 records from Extracellular DNA marine sediment Targeted Locus (Loci). 54 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 5 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 283 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 136 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 384 records from "Schwarzwassertal" bei Pobershau. 1932 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 5 records from Microfossil abundance of Hole 21-208. 217 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 928 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 1 records from Occurrence of mammalia relicts at site Ejstrup. 28385 records from Plan de vertebrados de la Patagonia. 2400 records from Springtales from lichen communities at Kollåsen in Norway. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 67 records from Planktic foraminifera distribution of sediment core TRI171-27. 4515 records from Distribution of planktic foraminifera of sediment core M35003-4. 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 3 records from Occurrence of mammalia relicts at site Igstadt I. 268 records from Planktic foraminifera abundance of Hole 22-217. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 304538 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 975 records from Danielsberg (Mölltal, Kärnten). 199 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 8 records from Nannofossil abundance of Hole 39-353A. 16988 records from LPO_PACA_2017_12_18. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 232661 records from Oklahoma Vascular Plants Database Provider. 350 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 3877 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 740 records from Targeting a portion of central European spider diversity for permanent preservation. 11463 records from Liste des pays par taxon spécimen TOGO. 10907 records from Census of species recorded during phytosociological surveys in Benin. 165 records from Nannofossil abundance of Hole 3-15. 2082 records from Foreign plant germplasm collections in Ghana. 2073 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 1558 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 439 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 18 records from Camiguin, Philippines Fauna. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 6556 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 41553 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 28 records from Biodiversity Surveys, South-east Arnhem Land. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 5 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 287 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 5809 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 86 records from Données naturalistes de Pierre-Alexis RAULT. 449 records from Wichita State University Collection. 376028 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 156 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 102 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 647 records from pbzt_insect_biodiversity. 7 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 281 records from NZCS Upper Tapanahony Expedition 1991. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 1 records from Oppia nitens. 24 records from Tanzanian Vertebrate Collection. 852 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 26185 records from Données de Mammifères enregistrées dans BazNat - Lot 1. 51 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 1168 records from Nannofossil abundance of Hole 17-167. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 5 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 1 records from Arthropoden aus südostalpinen Höhlen.. 289 records from bmhs_butterfly_collection. 2744 records from Distribution of major planktic foraminifer at Site 177-1090. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 3817 records from Microbial communities associated with ferromanganese nodules and the surrounding sediments. 122 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 1925 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 665 records from Planktic foraminifera counts of sediment core V04-8. 126 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 172 records from checklist-of-birds-of-zomba-mountain. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 110866 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 998 records from Plant of Folklore (KIDR-PL). 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 16 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 12 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 4644 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 13945 records from MfN - Fossil plants (Paleophytic). 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 603 records from Fossil (NSMK-FO). 2 records from First Jurassic grasshopper (Insecta, Caelifera) from China. 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 7 records from Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China. 6 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 128 records from Coleção de Nematoda do Museu Nacional - UFRJ. 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 4109 records from South Caribbean Diversity. 70 records from Total foraminifera counts of multinet M21/5_MSN731. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 1778 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 1123 records from Planktic foraminifera abundance of Hole 72-516F. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 1 records from Benthic foraminifera abundance of Hole 96-624. 7 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 11249 records from Heteroptera collections of SW Finland. 361 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 9 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 517 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 20588 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 2740 records from Fungi specimens of Saitama Museum of Natural History. 1543 records from Pollen record of sediment core Bokanjacko Blato 1. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 7 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 1129 records from Mollusca Collection of Saitama Museum of Natural History. 140 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 36 records from BIOMEO_2017_12_18. 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 211 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 841 records from Planktic foraminifera abundance of Hole 72-518. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 33 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 1 records from Oribates fusifer. 24 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 4 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 602 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 75 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 46680 records from Bosque Mesófilo de Montaña de México. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 22853 records from Données de Lépidoptères de Denis Vandromme. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 121176 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 29 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 488 records from Planktic foraminifera distribution of sediment core SU81-07. 5410 records from Collection ornithologique A. Maës. 31 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 2 records from New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey. 1645 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 89 records from Mammal specimens of Komatsu City Museum. 12 records from Urban Barcode Project - Fungi. 270 records from ACT and Southern Tablelands Weed Spotter. 41 records from Örtzemündung (Stedden). 1938 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 33892 records from National Stag Beetle Surveys (Great Stag Hunts). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 3291911 records from Eremaea. 14 records from Benthic foraminifera abundance of Hole 96-620. 86676 records from Marine Offshore Seabed Survey data held by JNCC. 100 records from Nanoplankton abundance at station GeoB2006-4. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 1490 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 27194 records from Natural History Museum Rotterdam (NL) - Chordata collection. 65 records from Occurrence of mammalia relicts at site Sütto_6. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 406575 records from Herbarium of Taiwan Forestry Research Institute. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 3698 records from NIWA Invertebrate Type Collection. 5 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 23 records from Ackerrain Plönhagen. 7066 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 258 records from Malawi-Histeridae-Biodiversity-Data. 1438 records from Planktic foraminifera abundance of Hole 7-64. 4439 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 26943 records from Collections of Phytoplankton at BGBM. 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 47 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 2851 records from Northern Gulf of Mexico Hypoxia can Alter Sediment Communities of Nitrifying Archaea. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 10 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 13947 records from The Vascular Plants Collection of the University of Goettingen. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 379 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 59 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 54 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 755529 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 814 records from flower availability 2008 Hainich. 1854 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 5 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 732 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 1125 records from Données naturalistes de Stéphane ORIO. 5327 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 10509 records from Andes to Amazon Biodiversity Program. 182790 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 665 records from Collection Echinodermata - ZMB. 651 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 186 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 28359 records from Collection Pisces SMF. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 12202 records from Pelagic Gulf of Mexico Targeted loci environmental. 8980 records from MEXU/Tipos de plantas vasculares. 32 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1642 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 442 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 8 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 242 records from Landschaftspflegehof (Berlin). 10 records from Bachpatenschaft Beeke. 354 records from SPC CoFish Invertebrates Observations Niue 2005. 84 records from Total foraminifera counts from M35/1_MSN1051. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 91 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 201 records from Total foraminifera counts of multinet M21/1_MSN606. 2917 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 694 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 17 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 251297 records from Estonian Nature Observations Database. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 589 records from Birds (NMNO-BI). 1095 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 17713 records from NCSM Mammals Collection. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 770 records from Nivå Bay species list, Zealand, Denmark. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 814 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 76262 records from Colección de Entomología del Instituto Alexander von Humboldt. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 164135 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 1 records from On the Chilopoda from Turkey. 2 records from Planktic foraminifera counts of multinet PS2616-5. 7814 records from Odonata de Veracruz. 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1441 records from Planktic foraminifera abundance of Hole 18-173. 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 279 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 1873 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 6393 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 635 records from CG04_2017_12_18. 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 127 records from Collection Ephemeroptera - SMF. 33 records from Microzooplankton abundance and biomass at station TT045_15-2. 10484 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 12 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 102476 records from Denver Museum of Nature & Science - Entomology. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 441 records from Relative abundance of planktic foraminifera in sediment core RC08-39. 16506 records from Database for alien invasive plants occurrences in Germany. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 35 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 793 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 84 records from Benthic foraminifera abundance of Hole 84-566C. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 704 records from (Table 17) Nannoplankton distribution in sediment core ANS3-T4. 1351 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 10212 records from Spider (NSMK-SP). 25488 records from OUPR - Herbário "Professor José Badini". 15 records from Nannofossil abundance of Hole 58-442B. 57218 records from National Biodiversity Data Bank. Observation records, 1900-2014. 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 200 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 12418 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 426 records from Données du Centre de la mer de Biarritz. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 18 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 92 records from Nottekanal, Klasse 7 - 10. 597 records from Percentages of planktonic foraminifera species in sediment core V30-40. 311 records from Nannofossil abundance of Hole 37-333. 5923 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 4845 records from Inventaire des Mollusques Sphaeriidae de France. 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 53 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 78 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 884 records from Sea shells of New South Wales. 2007 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 1409 records from Diatom assamblage in samples from sediment trap OG5. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 4222 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 6679 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 50 records from Flora und Fauna im Brexbachtal. 898985 records from MICROBIS database. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 191 records from Herpetofauna laguna El Tinije. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 123 records from Birdrace-Professorenteam-Münster. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 5710 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 36 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 248680 records from Swiss National Orthoptera Databank. 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 131 records from Planktic foraminifera counts at CTD station PS55/083-1. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 30091 records from BIOWIDE eDNA Fungi dataset. 45367 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 36162 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 13450 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 600 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 140 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 38 records from Was lebt in der Brutzwiese?. 59 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 2 records from Nannofossil abundance of Hole 4-26A. 96 records from Planktic foraminifera abundance of Hole 22-212. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 244 records from WildesMoor bei Schwabstedt. 443 records from Inventario herpetofaunístico del noroeste de Hidalgo. 391 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 3714 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 9366 records from ZooplanktonBeaufortSeaNOGAP2. 12 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 234 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 13 records from Microzooplankton abundance and biomass at station NBP97-08-23-6. 8 records from A taxonomic review of the genus Triscaedecia (Lepidoptera: Alucitidae) in the world fauna. 150 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 1386 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 11 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 2326 records from Jardín Botánico Atlántico, Gijón: JBAG. 26 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 751 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 559 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 1 records from A new species of Rock Gecko of the genus Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from Belitung Island, Indonesia. 562 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 128 records from Planktic foraminifera abundance of Hole 94-611. 168 records from (Table 1) Distribution of planktonic foraminifera species in Core ML2_66. 2 records from New ichneumonids (Hymenoptera, Ichneumonidae) from the Eocene Tadushi Formation, Russian Far East. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 3 records from Abundance of zooplankton in the Aral Sea. 105 records from Fish Fauna of Berlin. 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 12 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 1432 records from Phytoplankton abundance in surface water during cruise CD61. 29 records from Total foraminifera counts of trap L3_92_45. 2004 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 374 records from Medicinal potential of African plants (Togo). 91 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 8330 records from Nijmegen Natural History Museum (NL) - Herbarium. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 2573320 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 125055 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 282 records from MfN - Fossil invertebrates IIa. 105 records from Total foraminifera counts of trap L2_92_A42. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 1170 records from Département_du_Var_2017_12_18. 10 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 127 records from Wildlife Observations Bardon Hill 31.5.09. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 82 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 8 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 251 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 12939 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 92592 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 3139 records from CTD water column metabarcoding. 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 6 records from A revision of Holothuria (Halodeima) kefersteinii (Selenka, 1867) and the revival of Holothuria inornata Semper, 1868 from sea cucumbers collected in Mexico and Central America. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 2058 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 26642 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 39 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 51 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 227 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 2 records from Contributions to the palaeofauna of Ptinidae (Coleptera) known from Baltic amber. 173415 records from Hymenoptera specimen database of Kyushu University. 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 16 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 343 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 774943 records from Finnish Floristic Database (Literature Sources). 7 records from Analyses of the recent components in the sand fraction of sediment core PS1278-1. 174 records from The Myriapoda Collection of the National Museum of Nature and Science. 27 records from Review of the genus Elasmostethus (Hemiptera: Heteroptera: Acanthosomatidae) from the Korean Peninsula. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 2376 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B. 72185 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1766 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1 records from Microplankton counts and carbon biomass at station TT011_4-CTD46. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 7 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 7606307 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 8406 records from Conservatoire Botanique Pierre Fabre. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 175 records from Nannofossil abundance of Hole 41-366A. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 8 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 1483 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 451 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 1376 records from Bird Monitoring 2017, Meise Botanic Garden. 4358 records from Colecção Entomológica do Museu de História Natural de Maputo. 209 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 724 records from Heritage Trees of Ireland. 42 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 429 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 2215 records from Collection Polychaeta - ZSRO. 14061 records from imr_mareano_rpsledge. 21 records from Consolidated Checklist of Hard Corals of the Genus Acropora Oken, 1815 (Scleractinia: Acroporidae) in North Borneo, East Malaysia. 1 records from A new species of Eumeces Wiegmann 1834 (Sauria: Scincidae) from Iran. 17 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 182 records from Nannofossil abundance of Hole 55-433. 8 records from RISC Non-Native Species Records for Zebra Mussel. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 18 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 4207 records from CASES2003_2004. 3 records from Nouvelles fourmis de Madagascar.. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 39586 records from Fife Nature Records Centre combined dataset. 151 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 32 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 272 records from BIRDRACE Niederlausitz-Team. 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 1078 records from Pollen profile from Seminary School Basin. 25 records from Microzooplankton abundance and biomass at station TT043_4-1. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 52 records from Benthic foraminifera and algae abundance of Hole 35-325. 85 records from (Fig. 4) Nannofossil abundance of Cretaceous profile Pré-Guittard, SE France. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 313 records from BIRDRACE Gätkes Erben. 2990 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3304 records from Benthos counted on dredged samples during Valdivia cruise VA53. 1 records from Oribates calcaratus. 214 records from Total foraminifera counts of multinet M21/1_MSN608. 115 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 473492 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1000 records from Axel W. Erikssons African Bird Collection at Vänersborg Museum. 6613 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1882 records from Carabidae of the European North-East of Russia. 4019 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 262 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 6 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 1057 records from Palynological analysis of sediment core GeoB9508-5. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 35 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 131 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 6 records from Abundance of benthos infauna at station GIK23065-1. 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 593 records from Flux data of NU2_trap (Table A1). 4 records from Planktic foraminifera abundance of Hole 17-166. 2705190 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 16 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 228 records from Bishop's University Insect Collection (BUIC). 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 24 records from ALTERECO_2017_12_18. 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 476239 records from BioFokus. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15278 records from Anymals+plants - Citizen Science Data. 17943 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 6 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 5494 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 3383 records from Planktic foraminifera abundance of Hole 23-219. 71494 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1824 records from CNAN/Scorpiones. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 96 records from Total foraminifera counts of multinet M26/1_MSN845. 8649 records from Fossil (WSHN-FO). 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 13 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 35 records from Nannofossil abundance in sediment core PS1293-4. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 8 records from A new species of Orthosiphon (Lamiaceae) from Angola. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba (BID-AF2015-0066-REG). 281 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 2443 records from Cnidaria MZS. 458 records from Percentages of planktonic foraminifera species in sediment core V15-168. 26 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 7351 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 13 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 4816 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 14 records from Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 116 records from Nannofossil abundance of Hole 20-200. 907 records from Pollen profile Märchenwald B, Harz, Germany. 243 records from Thistles species and abundance. 60 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 6 records from Mammalia (JNHM-MM). 132 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 613 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 2 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 61 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 23 records from Abundance of benthos infauna at station GIK23055-1. 50 records from Site condition monitoring of lamprey in the Endrick Water SSSI and SAC, 2012. 17 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 22575 records from Living plant collection of Meise Botanic Garden. 143 records from Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA). 84 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction < 20µm. 10 records from Benthic macrofauna abundance of sediment core 13200-017. 4 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 528 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC08-145. 4051 records from Gunma Museum of Natural History, Fungi Specimen. 313 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 13979 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 37792 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 2 records from Kirchenforst. 252 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A. 13110 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 425 records from Percentages of planktonic foraminifera species in sediment core V22-38. 61 records from Range table from benthic foraminifera in ODP Hole 199-1215B. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 27 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 9658 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification possible. 1755 records from (Table 2) Pleistocene nannofossil range chart for ODP Hole 134-828A. 31 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 35 records from Nannofossil abundance of Hole 15-146A. 3 records from Lectotypification of three species of Silene sect. Italicae (Rohrb.) Schischk. (Caryophyllaceae). 3 records from Three new species of the cutthroat eel genus Dysomma, with comments on the variation of D. taiwanense (Anguilliformes: Synaphobranchidae). 4 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1335. 3 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 5 records from Revision of Chimarrogale (Lipotyphla: Soricidae) from Vietnam with comments on taxonomy and biogeography of Asiatic water shrews. 3990 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cardinalidae. 11 records from New records of deep-sea shrimps of family Solenoceridae Wood-Mason & Alcock, 1891 (Crustacea: Decapoda: Dendrobranchiata) from Southwestern Atlantic. 364 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 187017 records from UWFC Ichthyology Collection. 279 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 58 records from Mamíferos laguna El Tinije. 35 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 5546 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 22386 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 11119 records from Données naturalistes d'Anthony TURPAUD. 20 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 512 records from (Table 5) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841A. 614 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 50 records from A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia. 91253 records from CUMV Fish Collection. 112 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 6922 records from MUST, Insecta. 637398 records from Données ONF Faune-Flore-Fonge. 57 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 2116 records from Collection entomologique Pierre Lachiver. 50 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 48 records from Deutsche Schule Budapest. 18 records from Occurrence of mammalia relicts at site Trebacki krs. 2 records from ZUEC-POP - Coleção de Polyplacophora do Museu de Zoologia da UNICAMP. 72304 records from University of Tennessee Fungal Herbarium. 4 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 155713 records from University of Michigan Museum of Zoology, Division of Mollusks. 43 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 5 records from Occurrence of mammalia relicts at site Siebenlinden 3. 122 records from M. Burton (1936). The Fishery grounds near Alexandria IX – Sponges. Notes and Memoirs No.17. Department of Zoology, British Museum. Fisheries Research Directorate. Ministry of Commerce and Industry, Egypt.. 2103 records from Flora ficológica de la huasteca potosina. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 319 records from Range table from benthic foraminifers in ODP Hole 144-874B. 293608 records from Bird tracking - GPS tracking of Western Marsh Harriers breeding near the Belgium-Netherlands border. 613 records from Données acquises via le réseau du CBNBP. 2340 records from Type Specimen Database of Museum and Institute of Zoology PAS. 62161 records from DASSH Data Archive Centre Academic Surveys. 3784 records from Herbier de Wallis et Futuna. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 322 records from Occurrence of mammalia relicts at site Roc de Combe. 148 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 9 records from New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines. 9 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 513 records from Quoll sightings register for Nth QLD. 416 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 55 records from Highland biodiversity of Fanniidae (Insecta, Diptera): fourteen new species from the Andes and Central America. 109 records from Exkursion Ebertsheimer/Grünstädter Berg. 296318 records from University of Florida Invertebrate Paleontology. 6 records from Alburnus magnificus, a new species of bleak from the Orontes River drainage (Teleostei: Leuciscidae). 8 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 11 records from Données naturalistes de Thibault RAMAGE. 695 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 608 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 3 records from The spider genus Hersilia in Thailand, with descriptions of two new species (Araneae, Hersiliidae). 43 records from Vogelstimmenführung durch den Tiergarten. 2 records from Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae). 1 records from Physoschistura walongensis, a new species of loach (Teleostei: Nemacheilidae) from Arunachal Pradesh, northeastern India. 308 records from Echinodermata of Montenegro (South Adriatic). 9 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 185 records from (Table 2) Range chart of benthic and planktonic foraminifera of ODP Site 127-794. 4688 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 13 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 7 records from Five new species in the genus Leschenaultia Robineau-Desvoidy, 1830 (Diptera: Tachinidae) from Mato Grosso, Mato Grosso do Sul and Rondônia, Brazil. 35 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 51113 records from Atlas des Orthoptères et Mantides de France métropolitaine. 9 records from Six freshwater microturbellarian species (Platyhelminthes) in permanent wetlands of the Coastal Plain of southern Brazil: new records, abundance, and distribution. 257 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 1418 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 32706 records from UAM Bird Collection (Arctos). 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 353106 records from Dry Tortugas Reef Visual Census 2014. 16 records from A new species of chimaeroid, Hydrolagus alphus sp. nov. (Chimaeriformes: Chimaeridae) from the Galapagos Islands.. 6 records from Two new species of Loboschiza from Cambodia and Vietnam (Lepidoptera: Tortricidae: Olethreutinae: Enarmoniini). 24 records from Ostracoda abundance of Hole 48-406. 771 records from GEOECOLINK_2017_12_18. 219 records from Revision of the Mesoamerican species of Calolydella Townsend (Diptera: Tachinidae) and description of twenty-three new species reared from caterpillars in Area de Conservación Guanacaste, northwestern Costa Rica. 1698 records from UTEP Herpetology Osteology (Arctos). 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 85255 records from The Scottish Squirrel Database. 1186 records from Nannofossil abundance of Hole 75-530A. 24 records from Planktic foraminifera abundance of Hole 20-200A. 3 records from One new species and new record of the leafhopper genus Watara Dworakowska from Thailand (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 10 records from Collection Myriapoda - SNSD. 38 records from BB-Biodiversität a. 7248 records from DBRC Hemiptera species records 1969 to 2015. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 78612 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1357 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 1868 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 3546 records from Dorset SW Pilot species dataset. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 1924 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 324 records from (Table 2e) Nannofossil distribution chart of petroleum well Leeuwin-1. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 1 records from On two italian Lithobius species described by Silvestri with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda Lithobiidae). 320 records from Nannofossil abundance of Hole 24-237. 2080 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 13845 records from Cumbria Non Native Invasive Species. 5 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 596 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 78 records from Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula. 9 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 50 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 319 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 15 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 177 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 371 records from Benthic foraminifera and algae abundance of Hole 81-554A. 1056 records from Diatom assamblage in samples from sediment trap OG4. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 363 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 170543 records from England Non Native Species records 1965 to 2017. 134 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 18 records from Nannofossil abundance of Hole 3-18. 3 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 8 records from Microzooplankton abundance and biomass at station TT050_17-4. 2 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 225 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 8 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 3974 records from DBL_Life. 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 859 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 195 records from Pedestrian mammals census in W National Park. 4 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 29741 records from BLS Rare and Threatened Lichen Records: England. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 1123 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 6 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 116 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 1434 records from Nannofossil abundance of Hole 94-607. 122 records from Faunal assemblage of sediment core GS7603-8. 2171 records from Thrips (Thysanoptera) in Norway. 3 records from A new species of Homo from the Late Pleistocene of the Philippines. 69 records from Entdeckertour am Muldestausee 1/05. 2 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 89 records from Bird specimens of Ryukyu University Museum (Fujukan). 2007 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 2 records from A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 3 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 160 records from BIOTOPE_2017_12_18. 731 records from An updated record of Gaden Robinson's collection of Macro-moths of Fiji and Rotuma. 108 records from BIRDRACE Diesmal sehen wir mehr. 1134 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 7 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 977 records from Habitat and host related variation in sponge bacterial communities in Indonesian coral reefs and marine lakes. 3 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 1421 records from Weevils of Poland. 1764 records from Arachnida of Costa Rica (INBio). 205 records from Occurrence of some antimalarial plants from Cameroon. 24 records from Seawater carbonate chemistry, nutrients, and Calcidiscus leptoporus (strain RCC1135) growth rate and calcification rate during experiments, 2012. 3148 records from Ross A. Layberry, Collection. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 1212 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 201 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 119 records from Microfossil abundance of Hole 50-416A. 3 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 4 records from Microplankton abundance at bottle station SEPT-1999-K7. 24 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 8 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 247 records from Pollen analysis of sediment profile BLA00 from Blankensee. 7 records from Données naturalistes d'Olivier VILLEPOUX. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 160 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 274 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 104 records from Antarctic Parborlasia corrugatus. 12497 records from NCSM Non-molluscan Invertebrates Collection. 111529 records from The AAU Herbarium Database. 732 records from DSMZ Collection of Plant Viruses. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 2 records from Revision of the tree crickets of China (Orthoptera: Gryllidae: Oecanthinae). 3 records from New Earwigs in Protodiplatyidae (Insecta: Dermaptera) from the Middle Jurassic Jiulongshan Formation of Northeastern China. 96 records from BIRDRACE OAG Neuwerk. 52 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 11 records from Tanytarsini (Diptera: Chironomidae) from madicolous habitat in Southeast Brazil: new species and new records. 46 records from Planktic foraminifera counts of sediment core V26-124. 42 records from (Tab. 10) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-303A, Japanese Magnetic Lineations east of Japan. 13 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 41 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 36 records from Selz (Ingelheim am Rhein). 9 records from Four new species of Epacanthion Wieser, 1953 (Nematoda: Thoracostomopsidae) in intertidal sediments of the Nanji Islands from the East China Sea. 9594 records from Disko Fan Conservation Area in the Davis Strait (Eastern Arctic) - Epibenthic Megafauna Database. 398 records from Tsetse flies of East Africa update. 2647 records from SPC CoFish Fish Observations Nauru 2005. 83 records from European bison in Białowieża Primary Forest. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 2 records from Amphibia ZMK. 102 records from A Lichen Survey of the Ben Nevis Plateau. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 3 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 8 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 3 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 20755 records from pins. 1005 records from Collection Crustacea - KAUMM. 332 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 12 records from Revision of the genus Kailasha (Lepidoptera, Erebidae, Arctiinae) from Oriental region, with description of one new species. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 2256 records from Benthos, zoo- and phytoplancton data collected during the monitoring cruise of RV "Vladimir Parshin" in 1996.. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 1 records from Two new species of Xyalidae (Monhysterida, Nematoda) from the East China Sea. 519 rec
Keywords: GBIF; biodiversity; species occurrences